KnowledgeBoat Logo

Mathematics

Without using trigonometric tables, prove that:

sin 50°cos 40°+cosec 40°sec 50°4 cos 50° cosec 40° + 2=0\dfrac{\text{sin 50°}}{\text{cos 40°}} + \dfrac{\text{cosec 40°}}{\text{sec 50°}} - \text{4 cos 50° cosec 40° + 2} = 0.

Trigonometrical Ratios

16 Likes

Answer

To prove,

sin 50°cos 40°+cosec 40°sec 50°4 cos 50° cosec 40° + 2=0\dfrac{\text{sin 50°}}{\text{cos 40°}} + \dfrac{\text{cosec 40°}}{\text{sec 50°}} - \text{4 cos 50° cosec 40° + 2} = 0.

Solving, L.H.S. of the equation we get :

sin 50°cos 40°+cosec 40°sec 50°4 cos 50° cosec 40° + 2=0.sin (90° - 40°)cos 40°+cosec (90° - 50°)sec 50°4 cos 50° cosec (90° - 50°) + 2=0\phantom{\Rightarrow} \dfrac{\text{sin 50°}}{\text{cos 40°}} + \dfrac{\text{cosec 40°}}{\text{sec 50°}} - \text{4 cos 50° cosec 40° + 2} = 0. \\[1em] \Rightarrow \dfrac{\text{sin (90° - 40°)}}{\text{cos 40°}} + \dfrac{\text{cosec (90° - 50°)}}{\text{sec 50°}} - \text{4 cos 50° cosec (90° - 50°) + 2} = 0 \\[1em]

We know that,

sin (90 - θ) = cos θ

and

cosec (90 - θ) = sec θ

cos 40°cos 40°+sec 50°sec 50°4 cos 50° sec 50°+21+14×cos 50°×1cos 50°+224+20.\Rightarrow \dfrac{\text{cos 40°}}{\text{cos 40°}} + \dfrac{\text{sec 50°}}{\text{sec 50°}} - \text{4 cos 50° sec 50°} + 2 \\[1em] \Rightarrow 1 + 1 - 4 \times \text{cos 50°} \times \dfrac{1}{\text{cos 50°}} + 2 \\[1em] \Rightarrow 2 - 4 + 2 \\[1em] \Rightarrow 0.

Since, L.H.S. = R.H.S.

Hence, proved that sin 50°cos 40°+cosec 40°sec 50°4 cos 50° cosec 40° + 2=0\dfrac{\text{sin 50°}}{\text{cos 40°}} + \dfrac{\text{cosec 40°}}{\text{sec 50°}} - \text{4 cos 50° cosec 40° + 2} = 0.

Answered By

4 Likes


Related Questions